The role of pre-participation assessment (PPA) and screening in handball - Targett, S.; Bere, T.; Bahr, R. (Handball Sports Medicine, 2018)
The primary role of the pre-participation assessment (PPA) is to allow the team medical staff to get to know the current health status of the handball players in their team. This will usually include reviewing the player`s current medical problems and injuries, endeavouring to pick up unreported medical problems or symptoms, checking family history and reviewing medications and/or supplements.